2020
DOI: 10.1002/hep4.1457
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Prevalence in 50 U.S. States and D.C. by Sex, Birth Cohort, and Race: 2013‐2016

Abstract: Hepatitis C virus (HCV) infection is a leading cause of liver‐related morbidity and mortality, and more than 2 million adults in the United States are estimated to be currently infected. Reducing HCV burden will require an understanding of demographic disparities and targeted efforts to reduce prevalence in populations with disproportionate disease rates. We modeled state‐level estimates of hepatitis C prevalence among U.S. adults by sex, birth cohort, and race during 2013‐2016. National Health and Nutrition E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 38 publications
(91 reference statements)
5
67
1
Order By: Relevance
“…( 18‐20 ) A previous study showed that the prevalence of HCV and HBV infections in Minnesota are 7.8‐times and 40‐times higher in Blacks than non‐Blacks. ( 21,22 ) There are also state‐level differences in the prevalence of viral hepatitis and variation in state programs for viral hepatitis screening, access to care, and treatment. Therefore, racial/ethnic and state‐level variation in HCC incidence may improve with ongoing progress of the Viral Hepatitis National Strategic Plan goals to eliminate chronic viral hepatitis by 2030 ( 23 ) through universal screening for HCV, screening immigrants from endemic countries for HBV, and promoting linkage of infected individuals to treatment evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…( 18‐20 ) A previous study showed that the prevalence of HCV and HBV infections in Minnesota are 7.8‐times and 40‐times higher in Blacks than non‐Blacks. ( 21,22 ) There are also state‐level differences in the prevalence of viral hepatitis and variation in state programs for viral hepatitis screening, access to care, and treatment. Therefore, racial/ethnic and state‐level variation in HCC incidence may improve with ongoing progress of the Viral Hepatitis National Strategic Plan goals to eliminate chronic viral hepatitis by 2030 ( 23 ) through universal screening for HCV, screening immigrants from endemic countries for HBV, and promoting linkage of infected individuals to treatment evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…As such, our finding may be alarming as poorer adherence among Blacks can lead to reduced likelihood of achieving SVR, a population who already present lower SVR rates relative to Whites 6,23 . Furthermore, Blacks and people with other non‐White ethnicities represent the highest prevalence of individuals infected with HCV in the United States 24 and not effectively treating this portion of population may impede our efforts to eradicate HCV in the country. Overall, this finding may underline the need for implementing culturally appropriate components that are tailored for non‐White communities in order to achieve health equality and reduce health disparities in the context of HCV treatment.…”
Section: Resultsmentioning
confidence: 88%
“… 10 Bradley et al also analyzed NHANES laboratory data and found that persons born between 1945 to1965 had the highest prevalence of HCV infection, but that new infections are increasing among the young due to intravenous drug use. 13 The prevalence (per 100) and prevalence ratios (PRs in reference to > 1969 cohort) in Delaware per Bradley’s calculations can be viewed in Table 1 .…”
Section: Prevalence In Delaware Per National Health and Nutrition Examination Survey (Nhanes)mentioning
confidence: 99%
“…The CDC estimates that there are approximately 14 times more acute HCV infections than are reported, 14 and some suggest that figure may be an underestimate. 13 …”
Section: Prevalence and Associated Mortality In Usa And Delaware Per Delaware Department Of Health Reports And Centers For Disease Contromentioning
confidence: 99%
See 1 more Smart Citation